2019
DOI: 10.1080/15548627.2019.1643656
|View full text |Cite
|
Sign up to set email alerts
|

Dehydrin MtCAS31 promotes autophagic degradation under drought stress

Abstract: Drought stress seriously affects crop yield, and the mechanism underlying plant resistance to drought stress via macroautophagy/autophagy is not clear. Here, we show that a dehydrin, Medicago truncatula MtCAS31 (cold acclimation-specific 31), a positive regulator of drought response, plays a key role in autophagic degradation. A GFP cleavage assay and treatment with an autophagy-specific inhibitor indicated that MtCAS31 participates in the autophagic degradation pathway and that overexpressing MtCAS31 promotes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
72
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 80 publications
(73 citation statements)
references
References 68 publications
(108 reference statements)
1
72
0
Order By: Relevance
“…However, overexpression of MdATG18a enhances tolerance to drought stress in apple trees [53]. A recent study reported that autophagy improves drought tolerance in M. truncatula through degradation of the aquaporin MtPIP2;7, which interacts with the cargo receptor MtCAS31 [54]. Consistent with previous studies, our results revealed that the promoter of many MtATG genes contained the drought-related MBS cis-element (Fig.…”
Section: Discussionsupporting
confidence: 91%
“…However, overexpression of MdATG18a enhances tolerance to drought stress in apple trees [53]. A recent study reported that autophagy improves drought tolerance in M. truncatula through degradation of the aquaporin MtPIP2;7, which interacts with the cargo receptor MtCAS31 [54]. Consistent with previous studies, our results revealed that the promoter of many MtATG genes contained the drought-related MBS cis-element (Fig.…”
Section: Discussionsupporting
confidence: 91%
“…It can interact with the aquaporin MtPIP2;7 protein MtCAS31, which is a negative regulator of drought response. MtCAS31 promoted degradation of MtPIP2;7 in the autophagic pathway so that water loss was reduced and drought tolerance was improved under drought stress (Li et al, 2019). In this study, one TIP1-2-like gene (GeneID: 108338861) and one autophagy-related gene (GeneID: 108324651) were significantly up-regulated in drought tolerant variety under stress ( Table 1), suggesting that they play crucial roles in regulation seed germination to acclimatize to drought response.…”
Section: Discussionmentioning
confidence: 59%
“…On the other hand, overexpression of ATG18a in apple results in higher autophagy activity and increased drought tolerance, indicating the key role for autophagy in responses to drought (Sun et al, 2018). Recently, Medicago truncatula dehydrin MtCAS31 (cold acclimation-specific 31) was found to interact with both ATG8a and a negative drought stress regulator MtPIP2;7 to improve drought tolerance by facilitating autophagic degradation of MtPIP2;7, demonstrating that MtCAS31 functions as a positive regulator of drought-induced autophagy (Li et al, 2019b). Consistent with this idea, the Arabidopsis atg2 and atg7 mutants contain more oxidized proteins and are hypersensitive to both salt and osmotic stresses (Luo et al, 2017).…”
Section: Autophagy Can Be Induced By Abiotic Stressmentioning
confidence: 99%